Tracking finance for locally led climate action in Senegal - Callaghan, Charles; Chilambe, Pedro; Binge, Brenda; Lauriciano, Rabeca (2025)
Tree Aid and the Alliance of Bioversity International and CIAT are advancing research and advocacy to ensure that climate finance not only flows on a scale but also reaches communities at the subnational level where it is most urgently needed. The Alliance and Tree Aid are now working to develop a framework towards greater transparency on finance for locally led climate action. Initially, this work is focused on four countries – Ethiopia, Ghana, Kenya, and Senegal.